DEVELOPMENT OF PROJECT FINANCING BASED ON PUBLICPRIVATE PARTNERSHIP - Khaydarova Charos Nizamiddin kizi (Scholar Express Journals, 2024)
The article provides a comparative analysis of the work of foreign and domestic economists on financing projects based on public-private partnerships. A comparative table of the private partner’s participation in public infrastructure facilities was also studied. The types of funding sources for PPP projects have been identified. The activities of specialized organizations regulating PPP activities in the world have been analyzed. Proposals and recommendations have been developed for the development of project financing based on public-private partnerships
Keywords: Public-Private Partnership; Infrastructure Projects; Financing